Critical analysis on the use of SROI in the evaluation of social impact in social entrepreneurship initiatives (2019)
The inability of the State to address social problems such as poverty in all its ranges, unemployment, and the difficult access to education and health services, to mention just a few, has led to the institutionalization of the social sector in Mexico, wh